Opportunities for achieving the sustainable development goals through assessing health in environmental assessments. (30th September 2020) - Nowacki, J; Mekel, O; Martin-Olmedo, P; Cave, B
Abstract: The 2030 Agenda for Sustainable Development calls for tackling environmental risks at their root, that is, through a shift towards primary preventive actions and the promotion of healthy choices. Reducing the 13 million deaths resulting from environmental risks each year requires efficient scale-up of primary preventive action involving all key stakeholders, across all sectors. Decisions taken on the drivers of health risks should have the attainment and protection of good health as an explicit aim in key sectors such as energy, transport, housing, labour, industry, food systems and agriculture, water and sanitation, and urban planning. A key tool for such actions can be seen in Health Impact Assessments (HIAs) and an enhanced integration of health assessments into environmental impact assessments (EIA). In many countries worldwide, legally binding instruments exist which are concerned with assessing the impacts of policies, programmes, plans and projects on the environment to contributes to a high level of protection of the environment and human health. Within the European Union (EU) the EIA Directive 2014/52/EU names human health among the topics to be addressed when conducting an EIA. The amended EIA Directive also includes issues that are relevant to human health, for example, climate change and vulnerability (exposure and resilience) to major accidents and/or disasters. These amendments are relevant also beyond EU borders through, for example, the policies of the European Investment Bank. A paper recently developed by IAIA and EUPHA provides insights to the EIA Directive to raise awareness among health authorities and public health professionals on the potential for primary preventive actions and promotion of healthy choices outside the health sector. Key messages will be presented and further discussed with the audience on how achieving the 2030 Agenda can be supported through impact assessments and the enhanced involvement of health authorities.